2010
DOI: 10.1074/jbc.c109.057133
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clusterin Domain Involved in NF-κB Pathway Regulation

Abstract: Clusterin (CLU) is a ubiquitous protein that has been implicated in tumorigenesis, apoptosis, inflammation, and cell proliferation. We and others have previously shown that CLU is an inhibitor of the NF-B pathway. However, the exact form of CLU and the region(s) of CLU involved in this effect were unknown. Using newly generated molecular constructs encoding for CLU and various regions of the molecule, we demonstrated that the presecretory form of CLU (psCLU) form bears the NF-B regulatory activity. Sequence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…1) pathway [36]. A cytosolic function of CLU also correlates with its reported implication in the regulation of the NF-κB nuclear translocation and activity [39,40], while among the recently identified intracellular CLU interacting proteins are the erythrocytic protein Band-3 [41] and the molecular chaperone HSP60 [42]. …”
Section: Apolipoprotein J/clusterin (Clu)mentioning
confidence: 99%
See 1 more Smart Citation
“…1) pathway [36]. A cytosolic function of CLU also correlates with its reported implication in the regulation of the NF-κB nuclear translocation and activity [39,40], while among the recently identified intracellular CLU interacting proteins are the erythrocytic protein Band-3 [41] and the molecular chaperone HSP60 [42]. …”
Section: Apolipoprotein J/clusterin (Clu)mentioning
confidence: 99%
“…More recently, CLU gene expression was found to be induced during progression of primary osteoarthritis [67]. Interestingly, CLU seems to also directly intervene in NF-κB regulation, although its role remains debated; depending on the experimental model, CLU had either a negative [39] or a positive effect [40] on NF-κB activity.…”
Section: Functional Implication Of Clu In Ageing and Age-related Disementioning
confidence: 99%
“…Overall, it appeared recently that many previously reported functions are related to the intracellular forms of the protein, especially NF-B signaling and apoptosis. Indeed, intracellular level of CLU are essential for NF-B activity regulation (6,14), via its effect on the modulation of IB expression that seems to be linked to interaction to a ubiquitin ligase. As NF-B induced genes expression contributes to the pathogenesis of inflammatory diseases such as arthritis, CLU appeared to be a protein possibly involved in RA pathophysiology.…”
mentioning
confidence: 99%
“…Among the identified genes modulated in RA synovitis, the clusterin (CLU) gene appears to be a potential gene of interest because it has multiple functions related to apoptosis, inflammation, proliferation, and differentiation (4,5,7). The different functions of CLU depend on its final maturation and localization, cytosolic or nuclear, and involve NF-B signaling and juxtanuclear aggregates (3,6,14). The predominant form of CLU is a secreted heterodimeric protein of 80 kDa (sCLU) produced from the full-length RNA.…”
mentioning
confidence: 99%
“…However, the exact form of clusterin and the region(s) of clusterin involved in this effect were unknown. Essabani et al 32 has shown the pre-secretory form of clusterin (psClu) form bears the NF-kappaB regulatory activity. Neither the alpha-chain nor the beta-chain alone of clusterin had any NF-kappaB regulatory activity.…”
Section: Discussionmentioning
confidence: 99%